Comparison of a dimeric and a monomeric indium-quinolinato complex: synthesis, structure and photoluminescence. (19th January 2021) - Alexander, Orbett T.; Duvenhage, Mart M.; Kroon, Robin E.; Brink, Alice; Visser, Hendrik G.
Abstract : Two indium(iii ) complexes, mer -[In(Ox)3 ]·2H2 O (1) and [In2 (Ox)2 Cl2 -μ-[κ 2 -O, O′-(Ox)2 ]]·C7 H8 (2) (Ox = 8-hydroxyquinolinate), were synthesized and characterised for comparison by NMR, X-ray diffraction and photoluminescence. Abstract : Two indium(iii ) complexes, mer -[In(Ox)3 ]·2H2 O (1 ) and [In2 (Ox)2 Cl2 -μ-[κ 2 -O, O′-(Ox)2 ]]·C7 H8 (2 ) (Ox = 8-hydroxyquinolinate), were synthesized and characterised by multi-nuclear NMR in the solid and liquid states. The solid state 1 H-NMR spectra of both complexes confirmed the purity of the samples, but in solution it was found that 1 converted to the fac -isomer. The crystal structures of both complexes were determined by single crystal X-ray diffraction. As expected, the In–O bond distance for the bridging oxygen atom is the longest, 2.193 (13) Å. Solid state photoluminescence studies revealed that 1 and 2 showed emission at 530 nm and 500 nm, respectively, after excitation at 350 nm. Their respective quantum efficiencies were 13% and 20%. Lifetime measurements were conducted and the dimer showed a double exponential decay with two decay components recording 7.7 ns (30%) and 19.5 ns (70%), whereas the monomer recorded a mono-exponencial lifetime decay of 17.5 ns.